The Effect of Gamma Irradiation on the Growth Rate of Phosphorus and Potassium Solubilizer Multifunctional Microbes - Desak Ketut Tristiana Sukmadewi; Iswandi Anas; Ania Citraresmin (SEAS (Sustainable Environment Agricultural Science), 2021)
Phosphorus (P) and potassium (K) solubilizing microbes have an important role in accelerating the solubility process of P and K sources which are difficult to dissolve. The purpose of this research was to study the effect of gamma irradiation on the growth rate of P and K solubilizer multifunctional microbes. The microbes used in this study were P and K solubilizer multifunctional bacteria (Staphylococcus pasteuri) and the P and K solubilizer multifunctional fungi (Aspergillus costaricaensis). The microbes were irradiated with gamma rays at a dose of 0; 1; 2.5 kGy. Tests for the rate of bacterial growth were observed through the results of optical density and Total Plate Count (TPC), while fungi were observed through measurement of colony diameter and TPC. Gamma irradiation effects increasing the growth rate of P and K solubilizer multifunctional bacteria (1.0 BPK 5 and 2.5 BPK 5) based on optical density values. At the time of calculating the population using TPC method, the increase in bacterial growth rate tended to be shown by isolates 2.5 BPK 5. The effect of gamma irradiation on the growth rate of fungi was indicated by the colony diameter of the isolate 1.0 BPK 5 which was wider than the wild type isolate or isolate 2.5 BPK 5. TPC results on fungi also showed that gamma irradiation affected the growth rate of fungi at 24, 96, 120, and 288 hours incubation time. Keyword: Gamma irradiation; microbe; growth and fertilizer